A blockchain and gamification approach for smart parking - Ferreira, J.; Martins, A.; Gonçalves, F.; Maia, R. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2019)
City parking is increasingly complex and available parking spaces are scarce. Being able to identify a space to park their cars can lead many drivers to drive around the intended parking area several times, increasing traffic density and pollution. In this research we propose a collaborative blockchain solution with gamification for parking. Users collaborate to report free spaces and receive free parking minutes for their service to the community. In parallel, this approach can be used to collect beacon information from the parked vehicles and create a low-cost collaborative approach for managing a parking control process platform Blockchain that can handle this distributed process and the gamification platform increases users’ participation.